Cationic Supramolecular Hydrogels for Overcoming the Skin Barrier in Drug Delivery. Issue 4 (17th July 2017) - Limón, David; Jiménez‐Newman, Claire; Rodrigues, Mafalda; González‐Campo, Arántzazu; Amabilino, David B.; Calpena, Ana C.; Pérez‐García, Lluïsa
Abstract: A cationic bis‐imidazolium‐based amphiphile was used to form thermoreversible nanostructured supramolecular hydrogels incorporating neutral and cationic drugs for the topical treatment of rosacea. The concentration of the gelator and the type and concentration of the drug incorporated were found to be factors that strongly influenced the gelling temperature, gel‐formation period, and overall stability and morphology. The incorporation of brimonidine tartrate resulted in the formation of the most homogeneous material of the three drugs explored, whereas the incorporation of betamethasone resulted in a gel with a completely different morphology comprising linked particles. NMR spectroscopy studies proved that these gels kept the drug not only at the interstitial space but also within the fibers. Due to the design of the gelator, drug release was up to 10 times faster and retention of the drug within the skin was up to 20 times more effective than that observed for commercial products. Experiments in vivo demonstrated the rapid efficacy of these gels in reducing erythema, especially in the case of the gel with brimonidine. The lack of coulombic attraction between the gelator–host and the guest–drug seemed particularly important in highly effective release, and the intermolecular interactions operating between them were found to lie at the root of the excellent properties of the materials for topical delivery and treatment of rosacea. Abstract : What comes to pass : Passing through the skin barrier has become a main challenge in the topical treatment of dermatological diseases. These supramolecular hydrogels can effectively overcome this barrier and show promise in the topical treatment of rosacea. LMWG=low‐molecular‐weight gelator.